Preparation and evaluation of cellulose acetate butyrate and poly(ethylene oxide) blend microspheres for gastroretentive floating delivery of repaglinide - Rokhade, Ajit P.; Patil, Sangamesh A.; Belhekar, Anagha A.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2007)
In this study, hollow microspheres of cellulose acetate butyrate (CAB) and poly(ethylene oxide) (PEO) were prepared by emulsion-solvent evaporation method. Repaglinide was successfully encapsulated into floating microspheres. Various formulations were prepared by varying the ratio of CAB and PEO, drug loading and concentration of poly(vinyl alcohol) (PVA) solution. Encapsulation of the drug up to 95% was achieved. The microspheres tend to float over the simulated gastric media for more than 10 h. The micromeritic properties of microspheres reveal the excellent flow and good packing properties. The % buoyancy of microspheres was found to be up to 87. SEM showed that microspheres have many pores on their surfaces. Particle size ranges from 159 to 601 mu m. DSC and X-RD revealed the amorphous dispersion in the polymer matrix. In vitro release experiments were performed in simulated gastric fluid. In vitro release studies indicated the dependence of release rate on the extent of drug loading and the amount of PEO in the microspheres; slow release was extended up to 12 h. The release data were fitted to an empirical equation to compute the diffusional exponent (n), which indicated that the release mechanism followed the non-Fickian trend. (C) 2007 Wiley Periodicals, Inc.
Keywords: cellulose acetate butyrate; Controlled release; floating drug delivery; microspheres; repaglinide

Dual responsive cellulose microspheres with high solid-state fluorescence emission - Yadav, Prashant; Prajitha, K. P.; Dhaware, Vinita; Subramani, Mohan; Joy, Pattayil; Asha, S. K.; Shanmuganathan, Kadhiravan (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2020)
Materials that respond to multiple stimuli such as magnetic field and light are attractive for security and medical diagnostic applications. One of the major challenges in dual functional microspheres is that the presence of magnetic nanoparticles can quench fluorescence emission. Also, there is a probability of solid-state quenching due to the proximity of the fluorophore. We report here a facile approach to prepare cellulose microspheres with high solid-state fluorescence using 40 % tetrabutylammonium hydroxide (TBAH). The fluorescence quenching effect due to the presence of Fe3O4 nanoparticles and solid-state quenching due to aggregation of fluorophore was systematically investigated. Microspheres with the detectable magnetic response and fluorescence quantum yield as high as 0.57 (FMB 414) was obtained by optimizing the reaction conditions. Such a high quantum yield has not been reported before for dual stimuli-responsive fluorescent microspheres. The magnetic and fluorescent properties were found to be durable even after multiple washing cycles. These dual responsive cellulose microspheres can be added as security features to authenticate documents such as passports, degree certificates, currency notes, financial documents etc.
Keywords: Fluorescent; Magnetic; Microcrystalline cellulose; microspheres; Stimuli responsive microspheres; Tetrabutylammonium hydroxide